Outcomes of conservatively managed complex acetabular fractures in the frail and elderly one year post injury. Issue 2 (February 2020) - Baker, Gavin; McMahon, Samuel E; Warnock, Michael; Johnston, Andrew; Cusick, Laurence A
Highlights: This is the largest series of conservatively managed complex acetabular fractures in frail elderly patients in the published literature. The data confirms a high one year mortality (24%) and poor return to baseline mobilisation and residential status. There is no correlation between fracture reduction and post injury mobility or maintenance of mobility. Current operative solutions are considered too high risk in this elderly, medically frail cohort. Future innovations should focus on minimising the surgical impact and allowing immediate weight bearing mobilisation, equivalent to proximal femur fracture management. Abstract: Background: Acetabular fractures in the elderly are associated with high levels of morbidity and mortality. Despite advances in operative techniques, there remains a cohort of elderly, extremely frail patients with comminuted fractures who are considered unfit for surgery and are treated conservatively. We aim to assess mortality, mobility and radiological outcomes one-year post injury in this challenging cohort. Methods: We performed a review of the regional Fracture Outcome and Research Database for patients over 65 with associated type acetabular fractures which were treated conservatively. We collected data on demographics, fracture classification, pre-injury mobility and habitation, and length of acute hospital stay. Mobility status, habitation, radiographic result and mortality were also recorded at one-year post injury. Results: There were 49 patients with a mean age of 80 years. The mean estimated American Society of Anaesthesiologist (ASA) score was 3.1. 92% sustained a low energy injury, and the most common fracture pattern was anterior posterior hemi-transverse (84%). Mean acute hospital stay was 20 days and mortality was 24% at one year. 56% of patients maintained habitation in their own home and 35% returned to their premorbid level of mobility. Of the surviving patients, 30% had an 'excellent/good' reduction on x-ray at one year, 70% had a 'fair/poor' reduction. There was no correlation between fracture reduction and either one year mobility status or maintenance of mobility. Conclusions: The data confirms that conservatively managed complex acetabular fractures in the elderly, frail patient are associated with a significant reduction in mobility and living independence, a high level of mortality and poor radiological outcomes. Implications: Conservative management of this cohort is associated with poor outcomes and current operative solutions are unsuitable for this frail cohort of patients. Future developments should focus on minimising surgical insult and allowing weight bearing mobilisation to maximise the rehabilitation potential in this frail cohort.